Comparison of winning and record tactics in elite-level male middle-distance running - Kelemen, B.; Csanyi, T.; Revesz, L.; Benczenleitner, O.; Toth, L. (Journal of Physical Education and Sport, 2023)
The research aimed to investigate, over a longer period (1983-2018), how the most successful male middle distance runners (800m, 1500m) behave during Grand Prix races (R) and International Championship finals (W) in terms of pace and positioning. Using Kinovea 0.8.15 video analysis software, we analyzed split times and instantaneous position data per lap during 1500m and per 200m during 800m. In the 1500m, we analyzed 13 athletes' global competition medal-winning performances and personal best runs achieved in Grand Prix races (n=26). In the 800m, the top 3 finishers of 23 Grand Prix races and 25 Olympic and World Championship finals were investigated (n=144). Results: At both distances, the average race speed during the race was significantly (p < 0.05) better for R runs (800m: R 7.76 ± 0.04 m/s vs W 7.67 ± 0.08m/s; 1500m: 7.20 ± 0.04 m/s vs W 6.90 ± 0.15m/s). For the 800m R tactic, the average speed decreased steadily during the 200m stages. In both groups, there was a significant difference between the first and second laps. In terms of positioning, the athletes behaved similarly during the two tactics. 1500m: For the R tactics, the average speeds achieved between the first and last 400m were similar (7.30 ± 0.10 m/s; 7.34 ± 0.10 m/s), being significantly faster than the two middle laps of the steadily slow (7.03 ± 0.08 m/s; 7.09 ± 0.11 m/s). There was a significant difference between the average speeds achieved in the first 800m and last 700m of the distance for both the R and W tactics in favor of the second half of the distance, but the significance level was higher for W. During the W races, the two lowest average speeds of 400m were measured in the first two laps. The highest average speed was achieved during the last 400m (7.58 ± 0.19 m/s). The number of position changes was higher for W in all cases, with the largest difference for position changes between 800m and 1200m Conclusions: a slowing down (negative pacing) after a fast start at 800m yields the fastest results, while a more steady (inverted U-shaped) run at 1500m yields the record times. In Championship finals, later medalists do not try to control the pace in the first half of the distance in most cases, and cannot make up the time deficit in the second half.